2014
DOI: 10.1093/infdis/jiu121
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonality of Tuberculosis, Sunlight, Vitamin D, and Household Crowding

Abstract: Background. Unlike other respiratory infections, tuberculosis diagnoses increase in summer. We performed an ecological analysis of this paradoxical seasonality in a Peruvian shantytown over 4 years.Methods. Tuberculosis symptom-onset and diagnosis dates were recorded for 852 patients. Their tuberculosis-exposed cohabitants were tested for tuberculosis infection with the tuberculin skin test (n = 1389) and QuantiFERON assay (n = 576) and vitamin D concentrations (n = 195) quantified from randomly selected cohab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
3
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 39 publications
5
73
3
5
Order By: Relevance
“…Sunlight exposure is related to vitamin D production. Specifically, the highest incidence of tuberculosis has been found in areas where ultraviolet exposure is reduced and vitamin D deficiency is more prevalent [11], and low sunlight exposure has been associated with an increased incidence of tuberculosis several weeks later [10,14]. The consensus reached among nutritionists is that the serum 25 (OH) D concentration is quite low or absent above latitude 33°N in winter [39].…”
Section: Discussionmentioning
confidence: 99%
“…Sunlight exposure is related to vitamin D production. Specifically, the highest incidence of tuberculosis has been found in areas where ultraviolet exposure is reduced and vitamin D deficiency is more prevalent [11], and low sunlight exposure has been associated with an increased incidence of tuberculosis several weeks later [10,14]. The consensus reached among nutritionists is that the serum 25 (OH) D concentration is quite low or absent above latitude 33°N in winter [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been no data of the seasonal variation of serum 25 (OH) D concentrations of residents in Wuhan which is located at 30u N, we suppose that the serum 25 (OH) D concentrations are relatively low in winter of Wuhan residents. The result of one study showed that the serum level of 25-hydroxy vitamin D revealed about one month lag after the change of ultraviolet radiation [34], another study showed that the trough of 25-hydroxy vitamin D was in mid-winter [35]. Thus, the trough month of the serum level of 25-hydroxy vitamin D in Wuhan residents is assumed to be in February, one month behind the trough of ultraviolet radiation (January).…”
Section: Discussionmentioning
confidence: 99%
“…This decrease was predominantly caused by changes in social determinants such as improved living conditions 2,3 and nutrition. 4,5 TB rates worldwide are declining slowly and remain unacceptably high: a third of the world's population is estimated to be infected with TB and 1.5 million people died of TB in 2014, the majority of whom were impoverished people living in resource-constrained settings. 6 Thus, TB remains a social disease inextricably linked in a vicious cycle with poverty.…”
Section: Introductionmentioning
confidence: 99%